2020
DOI: 10.1039/d0mt00019a
|View full text |Cite
|
Sign up to set email alerts
|

Unexplored features of Ru(ii) polypyridyl complexes – towards combined cytotoxic and antimetastatic activity

Abstract: Promising antimetastatic compounds having high cytotoxicity against cancer cells combined with strong influence on their adhesion properties as well as inhibition of their metalloproteinases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 31 publications
2
28
0
Order By: Relevance
“…The detailed mechanism of such activity is still largely unknown; however, some of these compounds have been shown to strongly alter cell adhesion properties. MMP-2 and MMP-9 were considered among the postulated targets, and it was shown that some of the ruthenium polypyridyl complexes may inhibit their activity [19], while others may down-regulate their secretion [14,16]. In this study, for the first time, we investigate the relationship between the localization of Ru in the cell and the expression level of MMPs by analyzing subcellular fractions, which may strengthen the hypothesis of MMPs as potential targets for Ru polypyridyl complexes.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…The detailed mechanism of such activity is still largely unknown; however, some of these compounds have been shown to strongly alter cell adhesion properties. MMP-2 and MMP-9 were considered among the postulated targets, and it was shown that some of the ruthenium polypyridyl complexes may inhibit their activity [19], while others may down-regulate their secretion [14,16]. In this study, for the first time, we investigate the relationship between the localization of Ru in the cell and the expression level of MMPs by analyzing subcellular fractions, which may strengthen the hypothesis of MMPs as potential targets for Ru polypyridyl complexes.…”
Section: Introductionmentioning
confidence: 71%
“…Ruthenium polypyridyl complexes have been tested for many years for their use in anticancer therapy as cytotoxic agents [10][11][12]. Recently, ours and other studies have shown that ruthenium polypyridyl compounds in addition to their well-documented cytotoxic activity can affect various cell properties such as detachment, motility, invasion, colonization ability, and others that are crucial for metastasis formation and development [13][14][15][16][17][18][19]. The detailed mechanism of such activity is still largely unknown; however, some of these compounds have been shown to strongly alter cell adhesion properties.…”
Section: Introductionmentioning
confidence: 99%
“…Ru(II) compounds can not only suppress the primary tumor but also effectively inhibit malignant tumor metastasis. A series of recently synthesized Ru(II)-containing polypyridyl ligand complexes (Ru25-29 (Figure 6) [53] and Ru47 (Figure 9) [61]) showed…”
Section: Anti-metastasismentioning
confidence: 99%
“…A series of recently synthesized Ru(II)-containing polypyridyl ligand complexes ( Ru25–29 ( Figure 6 ) [ 53 ] and Ru47 ( Figure 9 ) [ 61 ]) showed anti-metastatic properties, which was attributed to their targeting ability to MMPs [ 53 ]. Ru25–29 bearing 2,2′-bipyridine substituted with a semicarbazone-2-formylopyridine moiety as one of the ligands and 4,4′-di-tert-butyl-2,2′-dipyridyl or 4,7-diphenyl-1,10-phenanthroline as auxiliary ligands have been studied for their effect on the adhesion properties of human A549 and pancreatic cancer cells [ 53 ]. All complexes enhanced the cell adherent properties and could directly inhibit the activity of MMP2 and MMP9 enzymes in vitro.…”
Section: Ru(ii) Complexesmentioning
confidence: 99%
See 1 more Smart Citation